Implementasi Good Corporate Governance Dalam Meningkatkan Kepercayaan Pada Perbankan Syariah - Moh. Agus Sifa'; Chusnu Fahruddin (Prodi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2021)
It is important to do so in order to further foster trust in society and improve the performance and progress of Islamic banking. The implementation of GCG in sharia institutions is important for the development of Islamic banking towards a more advanced direction. This is done because there is no guarantee that if an institution carries the name sharia, the institution will automatically implement good corporate governance. The research method used is a research library. The library research method is one of the methods that is part of the qualitative approach is library research (library research). Inspiration, this concept is needed in maintaining the objectivity of an organization or company in running a business by providing clear, accurate, easily accessible and understandable information and can be accounted for by all stakeholders in the organization or company. Accountability, this concept is needed to see the extent to which the performance has been produced by an organization and company. Responsibility, this concept reflects the responsibility of each individual or organization or company in complying with all tasks in the work, government regulations and policies relating to the business activities of an organization or company. Independence, this concept can be used as self-actualization for organizations and companies that can stand alone and have a competitive edge with their business environment. Fairness, this concept is needed to maintain company stability by maintaining fairness and equality for every member, stakeholder and other stakeholders in an organization or company with their respective portions.